2018
DOI: 10.1177/1071100718776021
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Impact of Adverse Events in Patients Undergoing Surgery for End-Stage Ankle Arthritis

Abstract: Level II, prospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…There were 6 works of literature excluded because they did not clearly compare the efficiency and safety of the two therapies (TAR and AAD), and another 7 studies were excluded because they could not be studied in the quantitative synthesis. Finally, 7 studies were included in the meta‐analysis because they met the eligibility criteria. The process of the selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 6 works of literature excluded because they did not clearly compare the efficiency and safety of the two therapies (TAR and AAD), and another 7 studies were excluded because they could not be studied in the quantitative synthesis. Finally, 7 studies were included in the meta‐analysis because they met the eligibility criteria. The process of the selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The follow‐up cycles were provided in all 7 studies, with the shortest one being 12.0 months and the longest being 77.0 months, while 5 studies showed the average age of patients. Five studies involved clinical outcome, 2 studies presented patient satisfaction, two studies compared complications, and four studies reported survival. Because of the lack of directly given data, the standard deviations were estimated for the clinical outcome part of the studies by Mehdi and Pedowitz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…lower falls self-efficacy). Previous publications have categorised the level of concern about falling as: low (scores of [16][17][18][19], moderate (scores of [20][21][22][23][24][25][26][27] and high (scores of 327 . This instrument has excellent internal and test-retest reliability (Cronbach's alpha=0.96, ICC=0.96) 326 .…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Nonetheless, there is a scarcity of scientific data in the area of ankle OA. Much of the research focus on ankle OA is related to the technical and clinical success of ankle surgical intervention [24][25][26][27][28][29] . Further, most studies to date have focused on people during the latter stage of the OA.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%